Automated Detection of Missing Links in Bicycle Networks. Issue 2 (21st March 2022) - Vybornova, Anastassia; Cunha, Tiago; Gühnemann, Astrid; Szell, Michael
Abstract : Cycling is an effective solution for making urban transport more sustainable. However, bicycle networks are typically developed in a slow, piecewise process that leaves open a large number of gaps, even in well‐developed cycling cities like Copenhagen. Here, we develop the IPDC procedure (Identify, Prioritize, Decluster, Classify) for finding the most important missing links in urban bicycle networks, using data from OpenStreetMap. In this procedure we first identify all possible gaps following a multiplex network approach, prioritize them according to a flow‐based metric, decluster emerging gap clusters, and manually classify the types of gaps. We apply the IPDC procedure to Copenhagen and report the 105 top priority gaps. For evaluation, we compare these gaps with the city's most recent Cycle Path Prioritization Plan and find considerable overlaps. Our results show how network analysis with minimal data requirements can serve as a cost‐efficient support tool for bicycle network planning. By taking into account the whole city network for consolidating urban bicycle infrastructure, our data‐driven framework can complement localized, manual planning processes for more effective, city‐wide decision‐making.